Comparison of semen analysis by manual and automated method (Journal of Pathology of Nepal, 2016)
Background: Semen analysis is used to evaluate male fertility. The aim of this study was to compare the results of semen analysis using manual method and automated sperm analyzer.Materials and Methods: This was a comparative study of 50 cases of semen analysis done in the Department of Pathology at the B.P. Koirala Institute of Health Sciences from March 2009 to March 2010. The automated sperm analyzer did not show the WHO parameters of patients who had functional sperm count (FSC) less than five hundred thousand (500,000). Semen analysis of each of the case included in the study was done by manual and automated method (using SQAII-P analyzer).Results: Out of 31 patients, the mean age of the patients was 28.56 years with youngest patient of 20 years and eldest of 45 year. Sensitivity and specificity was 100% in analysis of sperm concentration by both the methods. Sperm motility analysis showed 100% sensitivity and 81.81% specificity. Sperm morphology analysis showed 100% sensitivity and 34.48% specificity.Conclusion: It was observed that the automated method is much quicker and precise than the conventional, manual method for semen analysis.